Pengaruh Iklim Organisasi dan Stress Kerja Terhadap Turnover Intention Melalui Kepuasan Kerja Karyawan Bank Di Wilayah Surabaya - Cindy Maharani; Budiono Budiono (Jurnal Ilmu Manajemen, 2023)
The role of banking in the economy of a country is significant. All sectors related to finance always need bank services. Banking services in Surabaya are expected to increase economic prosperity in Surabaya. This study aims to determine and explain the effect of organizational climate and work stress on turnover intention through job satisfaction in banking employees in Surabaya. This type of causal research uses a quantitative approach with a population of all banking employees in Surabaya, both permanent and contract employees at commercial/conventional and private banks, with a sampling technique using accidental sampling with a total sample of 90 employees. The statistical analysis used in this study is Structural Equation Modeling (SEM) with the help of SMART-PLS 4.0 software. The results of this study indicate that the organizational climate has a positive effect on job satisfaction, work stress does not affect job satisfaction, job satisfaction harms turnover intention, the corporate environment harms turnover intention, job stress does not affect turnover intention, job satisfaction mediates the impact of organizational climate on turnover intention, job satisfaction does not judge the effect of work stress on turnover intention. Research implies that companies are expected to reduce turnover intention; companies can implement policies that are not detrimental to the company and employees, for example, paying attention to working hours so as not to cause stress. Companies need to create a sense of fairness and objectivity in employees.Keywords: Organizational Climate, Work Stres, Job satisfaction, Turnover intention.